Technical Note: An efficient daily QA procedure for proton pencil beam scanning. Issue 3 (19th February 2018) - Younkin, James E.; Shen, Jiajian; Bues, Martin; Robertson, Daniel G.; Mundy, Daniel W.; Clouser, Edward; Liu, Wei; Ding, Xiaoning; Stoker, Joshua B.
Abstract : Purpose: The aim of this work was to develop an efficient daily quality assurance (QA) program with strict tolerance levels for pencil beam scanning (PBS) proton radiotherapy featuring simultaneous dosimetric testing on a single, nonuniform field. Methods: A nonuniform field measuring beam output, proton range, and spot position was designed for delivery onto a Sun Nuclear Daily‐QA 3 device. A custom acrylic block permitted simultaneous measurement of low‐ and high‐energy proton ranges in addition to beam output. Sensitivities to output, range, and spot position were evaluated to quantitate the device's response. Reproducibility tests were used to identify and control sources of measurement error as well as to assess the QA procedure's robustness. This procedure was implemented in each of our four treatment rooms independently; 4–6 months of daily QA measurements were collected. Results: The 1% output, 0.5 mm range, and 1.5 mm spot position tolerances derived from preliminary tests were tighter overall than tolerances found in the literature and equivalent to the limits used for proton system commissioning. The simplicity and automation of the procedure reduced the time required for daily QA to 10 min per treatment room, and competition for beam between multiple treatment rooms was minimized. Conclusions: An efficient daily PBS QA procedure can be performed using a single, nonuniform field on a nondedicated QA device. A thorough quantitation of the device's response and careful control of measurement uncertainties allowed daily tolerances to match commissioning standards.